2013
DOI: 10.1021/jp409271r
|View full text |Cite
|
Sign up to set email alerts
|

Crystal-Plane-Dependent Etching of Cuprous Oxide Nanoparticles of Varied Shapes and Their Application in Visible Light Photocatalysis

Abstract: We report a simple, facile, surfactant-free chemical route to fabricate morphologically different Cu2O nanoparticles such as octahedron, truncated octahedron, hollow octahedron, cube, and sphere by varying the hydrolyzing agents, complexing agent, and reducing agents. Then the componential and morphological evolution of Cu2O nanoparticles have been studied independently, employing different etching agents such as aqueous NaOH, triethylamine (TEA), and oxalic acid solution. Particles of varied shapes and compos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
59
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(61 citation statements)
references
References 43 publications
2
59
0
Order By: Relevance
“…By studying the relative temporal positioning of the pump and probe pulse, features associated with polariton dynamics [13] are obtained. Absorption of near infrared light in excited cuprous oxide might possibly be useful for energy capture in a normally transparent region of photovoltaic [37][38][39][40] or photocatalytic devices [41][42][43][44].…”
Section: Discussionmentioning
confidence: 99%
“…By studying the relative temporal positioning of the pump and probe pulse, features associated with polariton dynamics [13] are obtained. Absorption of near infrared light in excited cuprous oxide might possibly be useful for energy capture in a normally transparent region of photovoltaic [37][38][39][40] or photocatalytic devices [41][42][43][44].…”
Section: Discussionmentioning
confidence: 99%
“…In the experiment, n = 1, D = 6.73 Â 10 À6 cm 2 s À1 , 23 V = 100 mV s À1 , and the calculated effective surface areas of the cubic and octahedral Cu 2 O-Nafion-GCE electrodes are 0.126 cm 2 and 0.142 cm 2 (Fig. A possible mechanism for the oxidation of glucose on the Cu 2 O-Nafion-GCE electrodes is follows: 24 Cu(I) + OH À -Cu(II) + e (2) Cu(II) + OH À -Cu(III) + e Moreover, based on the CV curves, it can be found that the current gradually increased from +0.3 V to +0.8 V, which corresponds to the Cu 2+ /Cu 3+ redox couple, 19 indicating that Cu 2 O crystals enable the electron transfer between the glucose and the GCE electrode.…”
mentioning
confidence: 93%
“…[39][40][41] This in turn leads to a higher concentration of hydroxyl radicals close to the nanocubes surface, which are the active species in the process of photodegradation of MO. 42,43 As our reaction is fully surface-controlled, the total rate is directly proportional to the surface concentration of the hydroxyl radicals, and thus increases. In detail, ESR spin trapping with DMPO was employed 44 to detect the concentration of hydroxyl radicals in illuminated solutions for pure Cu2O nanocubes as well as for Cu2O@PNIPAM core-shell nanoparticles.…”
Section: Resultsmentioning
confidence: 99%